Urban coral reefs: Degradation and resilience of hard coral assemblages in coastal cities of East and Southeast Asia - Heery, Eliza C.; Hoeksema, Bert W.; Browne, Nicola K.; Reimer, James D.; Ang, Put O.; Huang, Danwei; Friess, Daniel A.; Chou, Loke Ming; Loke, Lynette H.L.; Saksena-Taylor, Poonam; Alsagoff, Nadia; Yeemin, Thamasak; et al. (Marine pollution bulletin, 2018)
Given predicted increases in urbanization in tropical and subtropical regions, understanding the processes shaping urban coral reefs may be essential for anticipating future conservation challenges. We used a case study approach to identify unifying patterns of urban coral reefs and clarify the effects of urbanization on hard coral assemblages. Data were compiled from 11 cities throughout East and Southeast Asia, with particular focus on Singapore, Jakarta, Hong Kong, and Naha (Okinawa). Our review highlights several key characteristics of urban coral reefs, including “reef compression” (a decline in bathymetric range with increasing turbidity and decreasing water clarity over time and relative to shore), dominance by domed coral growth forms and low reef complexity, variable city-specific inshore-offshore gradients, early declines in coral cover with recent fluctuating periods of acute impacts and rapid recovery, and colonization of urban infrastructure by hard corals. We present hypotheses for urban reef community dynamics and discuss potential of ecological engineering for corals in urban areas. [Display omitted] •Corals and coral reefs near coastal cities are subject to a suite of intense stressors.•Sediment pollution constrains urban reefs to shallow depths and limits complexity.•Reefs in major cities declined early, and coral cover now fluctuates frequently.•Artificial structures near cities provide novel habitats that are colonized by coral.•Whether urban coral reefs constitute a unique ecosystem type needs to be tested.